On the interior ballistics of an underwater personal gun - Hoa, Nguyen Sy; Tran, Tran Van; Ha, Tran Thu (Vietnam Journal of Mechanics, 2016)
This paper deals with solving the problem of interior ballistics for a concrete personal underwater gun. The governing equations of the problem are carefully discussed because the water resistance force acting on the bullet is quite different from that of the air. These equations are used to create software for analyzing and designing an underwater gun. The calculated results are in very good agreement with the experimental data.